Neuropsychıatrıc dısorders assocıated wıth chıldhood ımmunologıc dysfunctıon - Ş. Gamze Korkmaz; Gülseren Keskin (Innowacje w Pielęgniarstwie i Naukach o Zdrowiu, 2023)
Introduction. These disease entities are known as pediatric neuropsychiatric syndromes because infectious pathogens other than streptococci have also been reported to be associated with neuropsychiatric symptoms. Pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection (PANDAS) and pediatric acute-onset neuropsychiatric syndrome (PANS).